A Survey on Machine Learning, Its Approaches and Challenges in Health Care - Pallavi Sood (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The area of machine learning research is constantly growing, offering several opportunities for investigation and application. ML is widely utilized in various applications like finance, life science, health care, transportation, education, security etc. The health care sector has long been an early adopter of and benefited greatly from technological advances. These days, machine learning plays a key role in many health related realms, including the development of new medical procedures, the handling of patient data and records, the treatment of chronic diseases, the findings of effects of various medicines, to discover patterns from medical data sources and provide excellent capabilities to predict diseases etc. An overview of machine learning-based approaches, learning algorithms, and applications in several healthcare domains is given in this study.